Thrombin stimulates the adherence of neutrophils to human endothelial cells in vitro. - Zimmerman, G A (1985)
Highly purified human thrombin stimulates the adherence of polymorphonuclear leukocytes (PMNs) to vascular endothelial cells (EC). When Indium-labeled PMNs were incubated with primary monolayers of cultured human umbilical vein EC, the basal adherence was 10 +/- 1% of the PMNs at 5 min. Addition of thrombin (2 U/ml) increased the mean adherence to 42 +/- 15%. Enhanced neutrophil adherence in response to thrombin was confirmed by experiments with unlabeled leukocytes, examined by phase contrast and scanning electron microscopy. The action of thrombin was on the EC, since it did not directly stimulate PMN adhesiveness when measured by aggregation or by adherence to nylon fiber columns. Furthermore, enhanced neutrophil adherence occurred when endothelial monolayers were treated with thrombin and washed before adding 111Indium (111In)-labeled PMNs. Thrombin that had been inactivated with antithrombin III and heparin did not enhance neutrophil adherence. Prothrombin, Factor Xa, and fibrinogen were also ineffective. The stimulated adherence of PMNs was maximal 5 min after incubation of the EC with thrombin, and decreased thereafter. The response was dose-dependent, with half-maximal stimulation at 0.2-0.25 U thrombin/ml. The enhanced PMN adherence caused by thrombin may result in part from the production of platelet-activating factor (PAF) by the stimulated EC since thrombin-stimulated EC synthesize PAF with a time course and concentration dependence that are similar to the time and concentration relationships for thrombin-stimulated PMN adherence, PAF itself promoted neutrophil adherence to the EC monolayers, and pretreatment of PMNs with PAF decreased the adherence stimulated by thrombin and PAF, but not adherence stimulated by N-formylmethionyl-leucyl-phenylalanine and C5a fragments, which indicates specific desensitization of PAF-mediated adherence. These studies demonstrate the endothelial cell-dependent stimulation of PMN adherence by thrombin, a novel mechanism of enhanced leukocyte adherence that may be important in interactions between the coagulation and inflammatory systems.